Analisis Retorika Dakwah K.H. Abdul Ghofur Dalam menyampaikan Pesan Dakwah - Furqon, Muchamad Raffi Tanzilul urqon; Hidayah, Luthfi; Rofiq, Ainur (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2025)
This research analyzes the da'wah rhetoric of K.H. Abdul Ghofur, the caretaker of Pondok Pesantren Sunan Drajat, who is known for his gentle and "dalang"-like (puppeteer-like) delivery style. Guided by QS. An-Nahl: 125 and Hadith HR. Bukhari no. 3461, da'wah is encouraged to use wisdom, good counsel, and polite debate. Rhetoric plays a crucial role in delivering clear and easily understood da'wah messages, especially in the digital era. This descriptive qualitative study employs Aristotle's rhetorical theory Invention, Dispositio, Elocutio, Memoria, and Pronuntiatio to examine K.H. Abdul Ghofur's da'wah style. Primary and secondary data were collected through observation, interviews, and documentation. The research findings include K.H. Abdul Ghofur's biography and educational background, along with an in-depth analysis of how he applies the five elements of Aristotelian rhetoric in his da'wah. This study also identifies the supporting and inhibiting factors of his da'wah rhetoric. The theoretical and practical benefits of this study are expected to provide a comprehensive understanding of contemporary da'wah rhetoric.